Development of a novel plasma scanning technique for high-quality anodic bonding. (29th February 2016) - Wu, Jim-Wei; Yang, Chii-Rong; Huang, Che-Yi
Abstract: Anodic bonding is a type of nonintermediate wafer bonding technique that has been widely used in microelectromechanical systems for sealing devices or assembling microstructures. However, the conventional anodic bonding method has a limitation. The specimens being bonded must typically be in contact with the anode and cathode electrodes during the bonding process. In general, the initial bonding position corresponds to the contact area of the two electrodes; subsequently, the bonded region gradually extends to cover the entire target region. Nevertheless, the traditional diffuse bonding method provides limited bonding efficiency in industrial applications. Therefore, this paper proposes a novel plasma bonding technique for 2D scanning anodic bonding. In this technique, the plasma is positioned to simultaneously heat and bond specimens. We conducted an experiment that entailed bonding 4-inch silicon/glass wafers by using N2 plasma. The results revealed that an almost bubble-free bonded interface and an average bonding strength exceeding 37 MPa were achieved for a bonding time of 15 min 53 s, bonding voltage of 2 kV, noncontact distance (between the cathode electrode and the bonding specimens) of 3 mm, variable raster scan path, scan speed of 3 mm s −1, and continuous scan steps of 2.5 mm in the x - and y -axes. A comprehensive series of experiments were performed to validate the bonding performance of the proposed technique.